EVALUATION OF SEED EMERGENCE, SEEDLING VIGOR ENHANCEMENT OF SOME POPULATIONS FROM SATUREJA BACHTIARICA WITH CHEMICAL, MECHANICAL AND PHYSIOLOGICAL TREATMENT - Alizadeh, M. A.; Arab, H.A.; Tabaie, R.; Nasiri, M.; Jafari, A.A. (Plant Breeding and Seed Science, 2016)
The seeds of 3 populations from Satureja bachtiarica were collected from three native vegetation areas (Simirom2, Sharkord and Yazd). The different treatments including: cold stratification, gibberlic acid (50 and 100 ppm) Potassium nitrate (0.2 and 0.4 percent). Physical scarification (sand paper), chemical scarification (Ethylic alcohol %70) and distilled water (control) were used for breaking dormancy of the seed samples. For greenhouse experiment, the seed samples were treated with treatments and then were sown in pots using randomize design with three replications. Emergence percentage, emergence speed, length of root and shoot, seedling length, root/shoot length ratio, vigor index, seedling fresh and dry weight, dry/fresh weight ratio were evaluated during 45 days of experiment. Comparing of population Semirom2 form savory of Bachtiary was higher than other population. It was concluded that effect of gibberlic acid and potassium nitrate was higher than physical scarification and chemical scarification comparing with control.